Effect of Salt on the Production of Xylanase in some Thermophilic Fungi - A. K. jaitly, Himani Yadav* and (Journal of Phytology, 2011)
The fungal isolates was studied for the production of xylanase at different salt level i.e., 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0%. Xylanase was produced by growing the test fungus in Bhat and Maheshwari medium supplemented with 1% xylan as carbon source at pH 6.0. All the fungal isolates showed an increase in their xylanase activity with the increase in salt concentration upto a limit, thereafter it decreased. Chaetomium thermophile (1.21 U/mg protein), Humicola insolens (2.69 U/mg protein), Rhizopus stolonifer (1.25 U/mg protein) showed their highest activity at 1.5% salt level, while Humicola fuscoatra (1.25 U/mg protein), Humicola grisea (1.29 U/mg protein), Sporotrichum thermophile (1.19 U/mg protein) showed the highest activity at 2% salt level. Mucor sp (2.79 U/mg Protein) exhibited the highest activity at lower salt level (1%). Thermoascus aurantiacus (1.26 U/mg Protein) showed the double salt optima for xylanase activity, one at 1.5% and the other at 2.5% salt level.